2013
DOI: 10.1093/treephys/tpt059
|View full text |Cite
|
Sign up to set email alerts
|

Climate signals derived from cell anatomy of Scots pine in NE Germany

Abstract: Tree-ring chronologies of Pinus sylvestris L. from latitudinal and altitudinal limits of the species distribution have been widely used for climate reconstructions, but there are many sites within the temperate climate zone, as is the case in northeastern Germany, at which there is little evidence of a clear climate signal in the chronologies. In this study, we developed long chronologies of several cell structure variables (e.g., average lumen area and cell wall thickness) from P. sylvestris growing in northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 35 publications
5
44
0
4
Order By: Relevance
“…Because of the existing mixed dendroclimatic signal, which is characteristic to the trees outside the extreme locations (upper timberline, limit of species range), further investigations on wood anatomical features that may allow for a more precise distinction of rain and thermal signal, are therefore necessary. Similar studies of Liang et al, 2013 have showed significant correlations between cell structure variables and temperature in northeastern Germany, representing the temperate climate zone. Also Helama et al, 2014 have demonstrated the usefulness of microdensitometric measurements for reconstruction of summer temperatures (using MXD data) and precipitation in the early part of the growing season (using earlywood variation) in southern Finland.…”
Section: Discussionsupporting
confidence: 67%
“…Because of the existing mixed dendroclimatic signal, which is characteristic to the trees outside the extreme locations (upper timberline, limit of species range), further investigations on wood anatomical features that may allow for a more precise distinction of rain and thermal signal, are therefore necessary. Similar studies of Liang et al, 2013 have showed significant correlations between cell structure variables and temperature in northeastern Germany, representing the temperate climate zone. Also Helama et al, 2014 have demonstrated the usefulness of microdensitometric measurements for reconstruction of summer temperatures (using MXD data) and precipitation in the early part of the growing season (using earlywood variation) in southern Finland.…”
Section: Discussionsupporting
confidence: 67%
“…Physiological processes that determine intra-annual density fluctuations (IADFs) are also closely linked with climate variability, especially in relatively dry environments (Campelo et al 2013;de Luis et al 2011;Rozas et al 2011). Overall, intra-annual dynamics of tree-ring formation (Oberhuber et al 2014) and anatomical variables are increasingly being considered in dendroclimatic reconstruction to highlight climategrowth relationships on sub-monthly time scales (Liang et al 2013;Panyushkina et al 2003;Szymczak et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…; 但随着树轮研究工 作的逐渐增多, 理想的树轮研究场所愈来愈少, 研 究工作不得不在一些响应不太敏感的非限制区开 展, 树轮研究遇到了前所未有的瓶颈 (Liang et al, (Campelo et al, 2010;Fonti et al, 2010;Abrantes et al, 2013;Liang et al, 2013;Venegas-González et al, 2015); 尤其是在非限制性地点, 木质部解剖特征具 有巨大的应用潜能 (Liang et al, 2013 (Fritts, 1976;Fonti et al, 2010;Liang et al, 2013) 部解剖特征被证实能够准确记录周边的环境变化且 具备气候重建的潜力 (February, 1994;Fonti et al, 2010;Abrantes et al, 2013;Liang et al, 2013;VenegasGonzález et al, 2015)。…”
Section: ) 已被广泛 用于全球变 化以及古气 候研究unclassified
“…"水分输导组织"为例 维管植物木质部的主要功能是输导水分与支撑 植物体 (Zimrnennann, 1983 (Wimmer, 2002;Giantomasi et al, 2009;Venegas-González et al, 2015)。管腔直径能够 直接影响木质部的导水能力, 根据哈根-泊肃叶定 Zimrnennann, 1983)。 土壤水分可利用性能够在年际或季节水平上 影响木材的形成 (Gruber et al, 2010;Eilmann et al, 2011;Vaganov et al, 2011;Wertz et al, 2013)。水分 胁迫(降水不足或高温)能通过多种途径直接或间接 地导致导管或管胞细胞变小或数量减小 (Eilmann et al, 2011;Vaganov et al, 2011), 如影响木质部同化 物的积累、控制细胞的分裂、扩大和分化等(图3) 宽度或密度等传统代用指标年表 (Fonti & García-González, 2004;Gea-Izquierdo et al, 2012;Fonti et al, 2013;Liang et al, 2013;Venegas-González et al, 2015), 尽管这些统计学参数并不代表年表记录环 境 信 息 的 强 弱 (Wimmer, 2002;Fonti & García-González, 2004;García-González & Fonti, 2008)。部 分年表质量统计特征已不太适合被用来描述细胞年 表质量 (Fonti & García-González, 2004;Giantomasi et al, 2009;Gričar et al, 2013;Venegas-González et al, 2015), 例如许多细胞年表样本总体代表性 ( & Fonti, 2006;Campelo et al, 2010;Fonti et al, 2010;Carrer et al, 2015), Fonti, 2006Fonti, , 2008。此外, 解剖 特征记录的气候信号还会因研究区域、树种、生境 或解剖特征的不同而不同 (Giantomasi et al, 2009;Matisons et al, 2012;Gričar et al, 2013;Liang et al, 2013;Martin-Benito et al, 2013;Castagneri et al, …”
Section: 木质部解剖特征记录环境信号的机理--以unclassified
See 1 more Smart Citation